Analisis Reduplikasi Bahasa Jawa Pada Novel Dom Sumurup Ing Banyu - Yunita Nugraheni (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2012)
Reduplication is one of the morfological process by which the stem or the root of the word is repeated. In this paper, the writer found the form of reduplication of Javanesse on the novel entitle Dom Sumurup ing Banyu. The research was done by collecting the data from the novel. The data classified into five groups of reduplication, namely; Dwilingga, Dwilingga salin swara, Dwipurwo, Dwiwasana, trilingga, and the combination of reduplication and affixation. Keywords: reduplication, stem, root, affixation